Enhancing soil ecosystem multifunctionality via carbon input and enzymatic catalysis in cover crops under antibiotic contamination - Ju Wang; Huanhuan Zhang; Jintao Yu; Xuechen Zhang; Mingjun Li; Peizhi Yang; Ziyan Li (Applied Soil Ecology, 2026)

Soil microbiome and ecological traits depending on fertilization and climate in organic input agricultural ecosystem - Weiwei Li; Bangyu Zheng; Shibiao Cai; Xuechen Zhang; Ziyan Li; Wei Zheng; Bingnian Zhai; Yakov Kuzyakov (Applied Soil Ecology, 2026)

Reinforcing mechanism of plastic film fibers in municipal solid waste: CT imaging of orientation distribution under various loading conditions - Yanan Sun; Jianyong Shi; Chao Liu; Yuchen Zhang; Gaojie Xu (Bulletin of Engineering Geology and the Environment, 2026)

Biofabrication and artificial intelligence strategies for investigating solid- and fluid-pressure mechanobiology in pancreatic ductal adenocarcinoma - Yahui Ding; Peiyuan Zhao; Yan Jin; Yan Li; Zifei Wang; Ye Lu; Yichen Zhang; Hongzhuan Chen; Weidong Zhang; Xin Luan; Min Tang (Cancer and Metastasis Reviews, 2026)

MDM2/X mediates reduced apoptosis in the plateau zokor: a mechanism of high-altitude adaptation - Mengchen Zhang; Yi Li; Huiqi Lin; Tianfu Yu; Fangyuan Xia; Mahanand Chatoo; Kexin Li; Honghao Yu; Eviatar Nevo; Jizeng Du; Yang Zhao; Xuequn Chen (Journal of Zhejiang University-SCIENCE B, 2026)

Bridging Aquaculture and Human Medicine: A Comprehensive Review of Zebrafish Models for Chronic Kidney Disease - Feng‐Yi Guo; Hao‐Yu Yang; Lan‐Chen Zhang; Xiang‐Ru Liu; Pan‐Pan Jia; De‐Sheng Pei (Reviews in Aquaculture, 2026)
Chronic kidney disease (CKD) poses a significant global health burden, necessitating robust animal models for mechanistic studies and drug discovery. Zebrafish offers unique advantages as a powerful models in kidney disease, including high‐throughput compatibility, optical transparency, and significant genetic and nephron homology with both humans and farmed teleosts. However, challenges, such as the species' potent regenerative capacity and a lack of standardized diagnostic thresholds, hinder their broad application. This review systematically summarizes four principal induction strategies: environmental stress, nephrotoxic chemical exposure, CRISPR/Cas‐based gene editing, and transgenesis. We further outline a validation pipeline that integrates functional assays, morphometrics, and histopathology, while advocating for cross‐laboratory harmonization. Additionally, we compare risk factors for CKD and CKD of unknown etiology (CKDu), emphasizing environmental contributors. Collectively, we propose zebrafish as a reproducible platform for aquaculture applications, specifically for nephropathy early‐warning systems and functional feed assessment, and for human therapeutic research. These standardized models hold great promise for high‐throughput drug screening and elucidating disease mechanisms, facilitating the translation of findings to both aquaculture and clinical medicine.

Nitrogen-salt interaction in Pennisetum giganteum: Effects on soil, rhizosphere, and ion transport processes - Peng Wang; Chen Zhang; Kok Sin Woon; Wenyu Li; Xu Pei; Mengxue Liu; Kun Zhang; Wenyan Li; Junkang Guo; Zhen Zhang; Yongtao Li (Applied Soil Ecology, 2025)

Bacterial–fungal interkingdom interactions mediate effects of biodiversity on soil carbon dynamics in wheat fields under long-term fertilization - Wenguang Li; Jiarui Zhao; Tianyu Feng; Xuechen Zhang; Ziyan Li; Wei Zheng; Bingnian Zhai (Applied Soil Ecology, 2025)

Hotspot enlargement and shortening hot moments in the rhizosphere to acquire labile phosphorus from fungal necromass in response to warming effects - Duyen Thi Thu Hoang; Ali Feizi; Viola Stelmach-Kardel; Kazem Zamanian; Xuechen Zhang; Marius Schmitt; Michaela A. Dippold; Agata Gryta; Magdalena Frąc; Bahar S. Razavi (Applied Soil Ecology, 2024)

Susceptibility of vegetation low-growth to climate extremes on Tibetan Plateau - Yichen Zhang; Songbai Hong; Dan Liu; Shilong Piao (Agricultural and Forest Meteorology, 2023)